PECULIARITIES OF TEACHING ENGLISH IN SECONDARY SCHOOLS IN UZBEKISTAN - Rustamova Shokhista Sharipovna (International Journal of Innovations in Engineering Research and Technology, 2021)
The opportunities for independent learning increase throughout Secondary School. Pupils are encouraged to assess their own work and to learn to formulate their own next learning steps. Pupils are encouraged to think critically and take risks in the classroom in order to develop problem-solving skills, for we believe that making mistakes is a vital part of the learning process. Project work is an essential component both individually and in groups. There is also a range of opportunities for pupils to pursue their areas of interest in greater depth both in school and through relevant enrichment experiences beyond the classroom.